Development of an Innovative Cell Isolation Method for the Investigation of Breast Cancer Pathogenesis and Angiogenesis for Experimental In Vitro And In Vivo Assays - Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2017)
Background Breast cancer is the world's most common cancer among women. Autologous lipotransfer is increasingly used for breast reconstruction following surgical removal of the tumour. In cell-assisted lipotransfer, the transplant is enriched with stem cells from adipose tissue (ADSC). Despite positive clinical results, there are some concerns regarding oncological safety due to transplanted stem cells. To date there are only a few breast cancer studies using primary cells from the same patient to enable further investigation into the complexity of cell-cell interactions in breast cancer in an experimental setting.Materials and methodsWe performed literature research on the topic of autologous lipotransfer. 5 different cell types (epithelial, mesenchymal cells, ADSC, endothelial cells, endothelial progenitor cells) were isolated from mammary (carcinoma) tissue or blood and were subsequently characterised for gene and protein expression as well as functional properties. The arteriovenous (AV) loop model in the rat was evaluated as a possible in vivo model for breast cancer pathogenesis and angiogenesis in this study.ResultsThe literature provided evidence for an in-vitro interaction between ADSC and cells of the mammary (carcinoma) tissue. In some clinical studies, certain subgroups of patients appeared to be exposed to an increased risk of tumour recurrence after lipotransfer, but in most studies no correlation between lipotransfer and tumour recurrence was found. Different cell populations, which differed significantly in terms of surface markers, gene expression and functional properties, were isolated from tissue of the same patient. Axial vascularised tissue was successfully generated in the AV loop model.ConclusionIn this study we were able to isolate different cell populations from the same patient, which reflect the heterogeneity of the tumour tissue. This enables a precise analysis of cell-cell interactions and their effects on tumour angiogenesis and pathogenesis in breast cancer. In combination with the AV loop model, this offers new possibilities to generate vascularised mammary carcinoma tissue as well as healthy mammary gland tissue in vivo as an optimal model for the clinical setting.
EVALuna2:32854